Perancangan Place Identity Ranu Grati Sebagai Upaya untuk Meningkatkan BrandAwareness - Yekti, Rendy Bramestian Pratama; Budiardjo, Hardman; Yurisma, Dhika Yuan (Jurnal Art Nouveau, 2017)
Pasuruan is one of the regencies in East Java province has many attractions but not yet terekpose perfectly. Pasuruan not only has a beautiful nature, but also a tourist destination worth to visit. The study was conducted using qualitative research is to conduct interviews, observation, documentation, and literature to obtain data to support the drafting. Data were analyzed using multiple stages of data reduction, data presentation and conclusion. the concept of